Bioreducible amphiphilic block copolymers based on PCL and glycopolypeptide as multifunctional theranostic nanocarriers for drug delivery and MR imaging. Issue 34 (12th April 2017) - Yang, Hui-Kang; Bao, Jun-Fang; Mo, Lei; Yang, Rui-Meng; Xu, Xiang-Dong; Tang, Wen-Jie; Lin, Jian-Tao; Wang, Guan-Hai; Zhang, Li-Ming; Jiang, Xin-Qing
Abstract : Amphiphilic diblock poly(ε-caprolactone)- b -glycopolypeptides (PCL–SS–GPPs) bearing disulfide bonds were synthesized from a clickable poly(ε-caprolactone)–SS–poly(2-azidoethyl-l -glutamate) diblock copolymer. Abstract : Amphiphilic diblock poly(ε-caprolactone)- b -glycopolypeptides (PCL–SS–GPPs) bearing disulfide bonds were synthesized from a clickable poly(ε-caprolactone)–SS–poly(2-azidoethyl-l -glutamate) diblock copolymer. Galactosyl and lactosyl sugar units as targeting ligands were conjugated to the polypeptide blocks via an efficient click reaction. The chemical structures of PCL–SS–GPPs were characterized by Fourier transform infrared spectroscopy and nuclear magnetic resonance analysis. Owing to their amphiphilic nature, these copolymers could self-assemble into spherical nano-sized micelles in an aqueous medium, as confirmed by fluorometry, transmission electron microscopy, and dynamic light scattering. The hydrophobic anticancer drug doxorubicin (DOX) and superparamagnetic iron oxide (SPIO) nanoparticles (NPs), as the magnetic resonance imaging (MRI) contrast agent, were simultaneously encapsulated in the hydrophobic core of the micelles via dialysis. The release profiles of encapsulated DOX from the SPIO/DOX-loaded PCL–SS–GPPs micelles were shown to be rapid in the presence of 10 mM glutathione (GSH) within 24 h, whereas in the absence of GSH, there was less than 35% DOX released from the PCL–SS–GPPs micelles in 24 h. Inverted fluorescence microscopy revealed the specific interaction between the sugars units on the PCL–SS–GPPs surface with the FITC-lectin. MTT assay demonstrated that the blank PCL–SS–GPPs micelles were nontoxic to the HepG2 cells, even for concentrations up to 500 μg mL −1, whereas the free DOX and DOX-loaded PCL–SS–GPPs micelles showed significant cytotoxicity against the HepG2 cells. The fluorescence images and flow cytometry tests revealed that DOX could be efficiently transported into HepG2 tumor cells by PCL–SS–GPPs micelles. The PCL–SS–GPPs micelles loaded with superparamagnetic iron oxide (SPIO) nanoparticles enabled excellent MRI contrast enhancement, thus confirming their effectiveness for MR imaging.